INTERNAL HERNIA FOLLOWING LAPAROSCOPIC ROUX-EN-Y GASTRIC BY-PASS: INDICATIVE FACTORS FOR EARLY REPAIR - SANTOS,Eduardo Pachu Raia dos (2019)
ABSTRACT BACKGROUND: Internal hernia (IH) following laparoscopic Roux-en-Y gastric bypass (LRYGB) is a major complication that challenges the surgeon due to its non-specific presentation and necessity of early repair. Delayed diagnosis and surgical intervention of IH might lead to increased morbidity of patients and impairments in their quality of life. OBJECTIVE: To evaluate the predictive factors for early diagnosis and surgical repair of IH after LRYGB. METHODS: This study analyzed 38 patients during the postoperative period of LRYGB who presented clinical manifestations suggestive of IH after an average of 24 months following the bariatric procedure. RESULTS: The sample consisted of 10 men and 28 women, with a mean age of 37.5 years and a mean body mass index (BMI) of 39.6 kg/m2 before LRYGB. All patients presented pain, 23 presented abdominal distension, 10 had nausea and 12 were vomiting; three of them had dysphagia, three had diarrhea and one had gastro-esophageal reflux. The patients presented symptoms for an average of 15 days, varying from 3 to 50 days. Seventeen (45.9%) patients were seen once, while the other 20 (54.1%) went to the emergency room twice or more times. Exploratory laparoscopy was performed on all patients, being converted to laparotomy in three cases. Petersen hernia was confirmed in 22 (57.9%). Petersen space was closed in all patients and the IH correction was performed in 20 (52.6%) cases. The herniated loop showed signs of vascular suffering in seven patients, and two (5.3%) had irreversible ischemia, requiring bowel resection. CONCLUSION: The presence of recurrent abdominal pain is one of the main indicators for the diagnosis of IH after LRYGB. Patients operated at an early stage, even with negative imaging tests for this disease, benefited from rapid and simple procedures without major complications.